The Problem of Providing Civilians with Collective Protection Facilities - Krupnik, Dorota (Roczniki Nauk Społecznych, 2025)
Ensuring the survival of civilians in collective protection facilities was not and is not a priority for state authorities. This is evidenced by the analysis of documents for the years 2011-2022. Current attempts to improve this situation, e.g. the inventory of shelters, places of hiding or temporary shelter carried out in 2023, do not eliminate many years of neglect in this area. The threats are real, and only the adopted Act on the Protection of the Population and Civil Defense of November 8, 2024 requires immediate action. Why is civil defense in Poland in such poor condition? Why do the circles responsible for it not have the courage to raise this issue effectively enough to ensure this safety? The aim of the article is to analyze the state of preparations undertaken in Poland in relation to the protection of civilians, especially in collective protection facilities, taking into account the current international geopolitical situation. The research problem was formulated as follows: to what extent and in what way has the civilian population in Poland been secured in collective protection facilities in the event of a potential crisis situation resulting from, for example, warfare? Current research on geopolitical factors influencing the country’s security shows that currently, the geopolitical security environment is characterized by uncertainty, unpredictability and sometimes lack of knowledge and impunity for decisions made and actions taken. Hipotetycznie zakłada się, że w takim stanie bezpieczeństwa międzynarodowego przygotowania organizacyjne, funkcjonalne i techniczne w obiektach ochrony zbiorowej są niewspółmierne do zagrożeń. Zapewnienie przetrwania ludności cywilnej w obiektach ochrony zbiorowej nie było i nie jest priorytetem dla organów państwowych. Świadczy o tym analiza dokumentów za lata 2011-2023. Obecne próby poprawy tej sytuacji, w tym przyjęta w 2024 r. ustawa o ochronie ludności i obronie cywilnej czy przeprowadzona w 2023 r. inwentaryzacja schronów, kryjówek czy czasowych schronów, nie eliminują wieloletnich zaniedbań w tym zakresie. Zagrożenia są realne. Do opracowania artykułu wykorzystano metody teoretyczne i empiryczne oraz narzędzia badawcze, w tym: metodę analizy dokumentów prawniczych i piśmienniczych, metodę porównawczą, metodę abstrakcji, zwłaszcza wykluczenia cech oraz metodę sondażu diagnostycznego, które wykorzystano do oceny stanu wiedzy i bezpieczeństwa w obiektach ochrony zbiorowej i działaniach pokrewnych.